Performance Research of Materials and Engineering Application of Overburden Strata Separation-Zone Grouting Technology - Wanpeng Huang; Huanyu Li; Gang Sun; Donghai Jiang; Yanfa Gao (Advances in Materials Science and Engineering)
To solve the ground subsidence problem associated with thick coal seam mining under the railway in the Tangshan Mine, the technology of overburden strata separation-zone grouting (OSSG) was proposed. Based on the analysis of the full height overlying strata structure in the range of the six working face areas of the second mining district, the spatial distribution characteristics of the separation zone within the overlying strata are obtained after fully mining the six working faces. Then, emphasis was placed on the selection ratio of grouting materials and the hydrodynamic properties of different grout types, and grouting grout with a high concentration, slow precipitation rate, and good stability was obtained by taking fly ash and local clay as aggregates. The designed grout concentration was approximately 40%; the bulk density was approximately 1.20; and the clay content in the aggregates was approximately 40–50%. The separation-zone grouting plan was designed for the six working faces, and continuous grouting technology with the characteristics of multiple separation zones within the full-height section with a large flow and a high concentration was proposed to form a complete grouting system and reasonable grouting process. After engineering verification, the technology has an ash injection ratio of 24.2%, a grouting ratio of 100.3%, and a reduction in the ground subsidence ratio of 51.5%, effectively reducing mining damage to the ground surface and ensuring the safe operation of ground surface railways. Simultaneously, this advancement improves the resource recovery rate of coal mines and provides greater benefits for mining enterprises.